Return to play after multiligament knee injuries in National Football League athletes - Bakshi, N. K.; Khan, M.; Lee, S.; Finney, F. T.; Stotts, J.; Sikka, R. S.; Bedi, A. (Sports Health: A Multidisciplinary Approach, 2018)
Return to play (RTP) of National Football League (NFL) athletes after isolated anterior cruciate ligament (ACL) tears has been reported. However, no studies have reported on RTP of NFL athletes after multiligament knee injuries. Hypotheses: NFL athletes with multiligament knee injuries have lower RTP rates and longer recoveries than athletes with isolated ACL tears. Second, athletes with ACL and medial collateral ligament (MCL) injuries will have higher RTP rates and shorter time to RTP than athletes with an ACL tear and posterolateral corner involvement. Study Design: Retrospective cohort study. Level of Evidence: Level 4. Methods: Publicly available NFL injury data were reviewed for all multiligament knee injuries incurred between 2000 and 2016 with RTP information. Athletes were excluded if RTP was limited for reasons unrelated to the injury. Extracted data included type of injury, RTP, time to RTP (days), number and percentage of games played, and performance. Results: A total of 50 NFL athletes with multiligament knee injuries met inclusion and exclusion criteria. The overall RTP rate was 64.0%. Athletes with ACL/MCL tears had an RTP rate of 70.8%, whereas athletes with ACL and posterior collateral ligament/lateral collateral ligament (PCL/LCL) tears had an RTP rate of 55.6% (P = 0.26). Mean time to RTP for all 50 athletes was 388.71 ± 198.52 days. The mean time to RTP for athletes with ACL/MCL injuries was 305.1 ± 58.9 days, compared with 459.2 ± 245.1 days (P = 0.004) and 609.3 ± 183.1 days (P < 0.0001) for those with combined ACL and PCL/LCL injuries and frank knee dislocations, respectively. Athletes with ACL/MCL injuries were more likely to return to prior performance level (43.5%) than those with ACL and PCL/LCL injuries (18.5%) (P < 0.001). Conclusion: The RTP rate for athletes with multiligament knee injuries is significantly less than the RTP rate for athletes with isolated ACL tears. In addition, athletes with ACL and MCL tears have a higher RTP rate, a significantly shorter time to RTP, and a greater likelihood of returning to prior performance than athletes with ACL and PCL/LCL tears. Clinical Relevance: Multiligament knee injuries significantly affect the ability of a football player to return to sport. ACL and MCL tears are associated with better RTP prognosis compared with ACL and PCL/LCL tears.